Topological Dirac Nodal‐Line Structure in Orthorhombic‐Ti3N2. Issue 3 (15th February 2018) - Yao, Ziwei; Zhang, Xiaoning; Feng, Xing; Wen, Bin
Abstract: As a new type of titanium nitrides phase, orthorhombic‐Ti3 N2 (o‐Ti3 N2 ) possesses coexistence of time‐reversal symmetry, spatial inversion symmetry, band inversion and negligible spin‐orbit‐coupling (SOC), hence it is expected to have special physical and chemical properties. In this work, its electronic and topological properties were systematically investigated by combing first‐principles calculations and Wannier tight‐binding analysis. It is found that o‐Ti3 N2 is a 3D topological nodal‐line material characterized by hornlike nodal lines in 3D momentum space. The "drumhead‐like" surface states exist on the (001) surface, while surface states possess the exotic single–double conversion, implying that o‐Ti3 N2 may process interesting surface transport properties. These features make o‐Ti3 N2 a new member in topological materials, with promising novel applications in electronic devices. Abstract : As a new type of titanium nitrides phase, o‐Ti3 N2 possesses coexistence of time‐reversal symmetry, spatial inversion symmetry, band inversion and negligible SOC, hence it is expected to be a topological nodal‐line material. Its electronic and topological properties were systematically investigated. Its complex nodal‐line structure and exotic surface states may lead to various interesting transport properties in o‐Ti3 N2 .